Elucidating ethylene-mediated physiology and biochemistry in selected climactic and non-climacteric fruits using e+® ethylene remover - Elmi, Fardusa (Cranfield University, 2013)
The presence of ethylene in a storage environment can undermine both quality and postharvest life of many fruits, often generating significant waste and associated economic losses. A demand for discovering alternative technologies capable of scavenging ethylene has led to the development of a new material, e+® Ethylene Remover, which has significant ethylene adsorption capacity. The material has been shown to remove ethylene to below physiologically active levels during fruit storage at 0-20 o C and consequently extend postharvest life for a variety of fresh produce types. Different formats incorporating e+® Ethylene Remover have been developed. Successful application of e+® Ethylene Remover in laboratory settings has created opportunities to test new formats of the product. To this end, work was conducted herein to attest whether e+® Ethylene Remover, which has been shown to maintain avocado (Persea americana cv. Hass) firmness in recent laboratory trials, could result in a meaningful extension of storage life in a commercial setting. It was shown that e+® Ethylene Remover coated sheets were a highly efficacious format for suppressing ethylene and extending storage life of imported avocado and pluot plums in a series of commercial trials. Moreover, the potency of the e+® Ethylene Remover treatment in retarding ethylene induced ripening was significantly enhanced when avocados were treated during the early stages of ripening. After a storage period of up to 31 days (5-6 o C), avocado fruits which had received an early treatment at source and then treated again in the laboratory were significantly more firm and greener compared to fruits treated following 5 weeks of transit alone . Strawberry is regarded as non-climacteric fruit; nevertheless, exogenous ethylene can negatively influence postharvest life. The low ethylene produced by non-climacteric fruits has been generally ignored and research reporting on the involvement of ethylene in these fruits is typically devoid in the literature. To this end, application of a highly sensitive laser based photoacoustic ethylene detector has revealed a possible role of ethylene in determining the postharvest life of strawberries. Moreover, fruit quality parameters including disease incidence, sugars, organic acids, phenolic compounds and plant phytohormones/metabolites were found to be profoundly affected by ethylene and likewise the removal of ethylene. Storage of strawberries in the presence of e+® Ethylene Remover was associated with lower disease incidence, significantly less red fruits and higher ascorbic acid content. In contrast, ethylene and 1-methylcyclopropene (1-MCP) treatments resulted in the higher postharvest disease. Ethylene-treated fruits were associated with lower level of sucrose and higher simple sugars (fructose and glucose) suggesting a role of ethylene in promoting the rate of senescence and concomitant reduced postharvest quality of strawberries. Changes in ABA, ABA metabolites and auxins within different tissues of ripe strawberry during storage were investigated. ABA was more abundant in the flesh than in the achenes, while auxins were undetectable in the flesh tissue. Auxins indole-3-acetic acid (IAA) and the conjugated form indole-3-acetylaspartic acid (IAAsp) were detected in high concentrations in the achenes and were affected by ethylene and storage length.